Proposta de ação pedagógica interdisciplinar: integrando a língua inglesa a um projeto de leitura para a 5ª série do ensino fundamental - Flores, Cristiane Barasuol (Universidade do Vale do Rio do Sinos, 2010)
The aim of this study is to propose an interdisciplinary educational action integrated to a reading project for the 5th grade of an elementary school that is part of the municipal public school system in Caxias do Sul. The data were obtained from observation recordings in pedagogical meetings, individual meetings with the pedagogical coordinator, and informal conversations among teachers. The data have been further related to some school documents and the response by the teachers to the proposal presented. The findings suggest that the school shows some positive aspects towards interdisciplinary work, as well as some limitations that prevent it from happening adequately. The proposed action aims to detail educational activities of an interdisciplinary project with the support of a theoretical background in order to create conditions for actual interdisciplinary.
Keywords: gêneros textuais; interdisciplinaridade; pedagogia de projetos; interdisciplinary; text genres; project approach; Letras e Artes; Lingüística